Analisis corporate social responsibility (csr) dan good corporate governance (gcg) terhadap tax avoidance pada perusahaan manufaktur sektor industi barang konsumsi yang terdaftar di bei - Gracia Am; Siti Friantin (IHSA Institute, 2023)
This study aims to examine the effect of corporate social responsibility (CSR) and good corporate governance (GCG) on tax avoidance in manufacturing companies in the consumer goods industry sector which are listed on the IDX for the 2019-2021 period. This research uses quantitative methods and purposive sampling techniques with secondary data on financial statements and annual reports. Multiple linear regression is used as an analysis model. The results of the study show that partially corporate social responsibility and audit committees have no significant negative effect on tax avoidance, the board of commissioners has a significant positive effect and the board of independent commissioners has a significant negative effect. The ability of CSR, as well as the components of GCG (board of commissioners, independent commissioners, audit committee) in explaining tax avoidance of 32.5% is indicated by an adjusted R2 value of 0.325. While the remaining 67.5% is influenced by other variables outside of this study.